Enhancing Entrepreneurial Mindsets through Pragmatic Entrepreneurship Education: A Study of Chemistry Undergraduates in Nigerian Universities - ABIDOYE, Florence Omosholape; ALADESUYI, David Adeyemi; ABIDOYE, Adekunle Omotayo (Ilorin Journal of Education, 2025)
The evolving landscape of professional environments necessitates a departure from traditional education paradigms towards a more integrated and entrepreneurial approach. This study investigated enhancing entrepreneurial mindsets through pragmatic entrepreneurship education: A study of chemistry undergraduates in Nigerian Universities. The study employed a descriptive survey methodology, sampling 240 chemistry undergraduates from Ekiti State University, Ado-Ekiti. Data obtained using questionnaire was analysed using percentage, mean, and SD. The instruments were duly validated by experts. The reliability coefficient of the instrument was 0.77. Key findings highlight that entrepreneurial internship programs, business incubation initiatives, practical applications, supportive regulatory environments, cross-disciplinary collaborations, and entrepreneurship competitions significantly enhance the entrepreneurial mindset. The study concludes that embedding these pragmatic practices into the chemistry curriculum can better align education with market demands, potentially mitigating unemployment among graduates. The study recommends that universities should collaborate with industries to offer internship opportunities where students can apply theoretical knowledge to real-world business scenarios.